MAGIC AND WITCHCRAFT IN CURRENT INDONESIAN HORROR FILMS - Diah Agung Esfandari (Lingkar Studi Komunikasi (LISKI), 2016)
During the former President Soeharto’s regime (or the New Order) in 1966-1998, films were vehicles for the creation of a national culture intended to implement its development policies and more generally its authoritarian rule.  There were guidelines on what to say, what not to say and who could speak in which medium.  Every film produced during the New Order, had a narrative structure that moved from order through disorder to a restoration of the order.  However, since the fall of the New Order, there is a re-emergence of Javanese cultural identity (known as kejawen or kebatinan) through the second boom of Indonesia’s horror film in cinemas.  As Mulder (2005) explained, the revival and vitality of ‘kebatinan’ mysticism in the immediate post-independence period can best be seen as a search for cultural expression and identity in a time of transition and change.  One of the examples of Indonesia’s current horror film is Jelangkung (2001) which is based on a Javanese folklore, and has reawakened once again the overall Indonesia’s film industry that has been stagnant since the monetary crisis in 1996.  This paper aims to find out how Indonesian horror films (2001-2008) more specifically: Jelangkung (2001), Kuntilanak (2006) and Titisan Naya (2008) have provided a significant means for the reassertion of Javanese cultural identity.  It is a part or chapter of a bigger paper or dissertation that is still an ongoing process.